2017
DOI: 10.1021/acs.jafc.7b03014
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Spectroscopy Uncovering the Effects of Cu Based Nanoparticle Concentration and Structure on Phaseolus vulgaris Germination and Seedling Development

Abstract: Nanoparticles properties such as solubility, tunable surface charges, and singular reactivity might be explored to improve the performance of fertilizers. Nevertheless, these unique properties may also bring risks to the environment since the fate of nanoparticles is poorly understood. This study investigated the impact of a range of CuO nanoparticles sizes and concentrations on the germination and seedling development of Phaseolus vulgaris L. Nanoparticles did not affect seed germination, but seedling weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 49 publications
2
34
1
3
Order By: Relevance
“…Palavras Chave: nanotecnologia; Solanaceae; inseto; transferência trófica; espectroscopia por fluorescência de raios-X In the last 20 years, there has been great development and use of nanotechnology in the electronics, automotive, energy, medicine, and agricultural sectors (Paschoalino et al 2010;Vance et al 2015). Several academic studies suggest that nanoCuO, nanoZnO, nanoCeO 2 , and nano TiO 2 can be used in fertilization by seed treatment (Duran et al 2017), or broadcast on foliage and soil (Raliya et al 2018). Additionally, they also may be applied as pesticides (Khot et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Palavras Chave: nanotecnologia; Solanaceae; inseto; transferência trófica; espectroscopia por fluorescência de raios-X In the last 20 years, there has been great development and use of nanotechnology in the electronics, automotive, energy, medicine, and agricultural sectors (Paschoalino et al 2010;Vance et al 2015). Several academic studies suggest that nanoCuO, nanoZnO, nanoCeO 2 , and nano TiO 2 can be used in fertilization by seed treatment (Duran et al 2017), or broadcast on foliage and soil (Raliya et al 2018). Additionally, they also may be applied as pesticides (Khot et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The μ-XRF analysis of W-NP-exposed roots showed a homogenous distribution of Cu in the tissues, while μ-XANES analysis of W-NP-exposed roots showed near complete transformation of CuO to Cu (I)-sulfur and oxide complexes in the tissues. Duran et al (2017) showed that CuO-NPs did not affect seed germination of Phaseolus vulgaris L., but seedling weight gain was promoted by 100 mg Cu L -1 and inhibited by 1000 mg Cu L -1 of 25 nm CuO and CuSO 4 . The μ-XRF analysis showed that most of the Cu taken up remained in the seed coat with Cu hotspots in the hilum.…”
Section: Toxicity On Aquatic Animalsmentioning
confidence: 95%
“…In this context, X‐ray fluorescence (XRF) spectroscopy arises as an alternative and promising technique for foliar diagnosis, presenting attractive features such as multielemental and simultaneous capabilities, nondestructive analysis, minimal or no sample preparation, and equipment portability. The samples can be analyzed as powders, pellets, or even under vivo conditions …”
Section: Introductionmentioning
confidence: 99%